Depending on Its Nano-Spacing, ALCAM Promotes Cell Attachment and Axon Growth - Thelen, Karsten; Jaehrling, Steffen; Spatz, Joachim P.; Pollerberg, G. Elisabeth (PLOS ONE, 2012)
ALCAM is a member of the cell adhesion molecule (CAM) family which plays an important role during nervous system formation. We here show that the two neuron populations of developing dorsal root ganglia (DRG) display ALCAM transiently on centrally and peripherally projecting axons during the two phases of axon outgrowth. To analyze the impact of ALCAM on cell adhesion and axon growth, DRG single cells were cultured on ALCAM-coated coverslips or on nanopatterns where ALCAM is presented in physiological amino-carboxyl terminal orientation at highly defined distances (29, 54, 70, 86, and 137 nm) and where the interspaces are passivated to prevent unspecific protein deposition. Some axonal features (branching, lateral deviation) showed density dependence whereas others (number of axons per neuron, various axon growth parameters) turned out to be an all-or-nothing reaction. Time-lapse analyses revealed that ALCAM density has an impact on axon velocity and advance efficiency. The behavior of the sensory axon tip, the growth cone, partially depended on ALCAM density in a dose-response fashion (shape, dynamics, detachment) while other features did not (size, complexity). Whereas axon growth was equally promoted whether ALCAM was presented at high (29 nm) or low densities (86 nm), the attachment of non-neuronal cells depended on high ALCAM densities. The attachment of non-neuronal cells to the rather unspecific standard proteins presented by conventional implants designed to enhance axonal regeneration is a severe problem. Our findings point to ALCAM, presented as 86 nm pattern, for a promising candidate for the improvement of such implants since this pattern drives axon growth to its full extent while at the same time non-neuronal cell attachment is clearly reduced.